What does anisotropy measure? Insights from increased and decreased anisotropy in selective fiber tracts in schizophrenia - De Erausquin, Gabriel A.; Alba-Ferrara, Lucia (Frontiers in Integrative Neuroscience, 2013)
Schizophrenia is a common, severe and chronically disabling mental illness of unknown cause. Recent MRI studies have focused attention on white matter abnormalities in schizophrenia using diffusion tensor imaging (DTI). Indices commonly derived from DTI include (a) mean diffusivity, independent of direction, (b) fractional anisotropy (FA) or relative anisotropy (RA), (c) axial diffusivity, and (d) radial diffusivity. In cerebral white matter, contributions to these indices come from fiber arrangements, degree of myelination, and axonal integrity. Relatively pure deficits in myelin result in a modest increase in radial diffusivity, without affecting axial diffusivity and with preservation of anisotropy. Although schizophrenia is not characterized by gross abnormalities of white matter, it does involve a profound dysregulation of myelin-associated gene expression, reductions in oligodendrocyte numbers, and marked abnormalities in the ultrastructure of myelin sheaths. Since each oligodendrocyte myelinates as many as 40 axon segments, changes in the number of oligodendrocytes, and/or in the integrity of myelin sheaths, and/or axoglial contacts can have a profound impact on signal propagation and the integrity of neuronal circuits. Whereas a number of studies have revealed inconsistent decreases in anisotropy in schizophrenia, we and others have found increased fractional anisotropy in key subcortical tracts associated with the circuits underlying symptom generation in schizophrenia. We review data revealing increased anisotropy in dopaminergic tracts in the mesencephalon of schizophrenics and their unaffected relatives, and discuss the possible biological underpinnings and physiological significance of this finding.